Functional reconstruction of lower eyelid using paramedian forehead flap combined with frontalis muscle and periosteum - Riku Katayama; Takako Fujii; Chie Kanayama; Hisashi Sakuma (Archives of Plastic Surgery)
Both cosmetic and functional aspects are important in the reconstruction of lower eyelid tissue defects. In this case report, we describe a two-stage reconstruction of a skin defect, including the orbicularis oculi muscle, after resection of a basal cell carcinoma using a paramedian forehead flap combined with the frontalis muscle and periosteum. In the first stage, the paramedian forehead flap, including the frontalis muscle and periosteum, was elevated, the periosteal flap was fixed to the outer orbital periosteum to lift the lower eyelid, and the skin flap, including the frontalis muscle, was sutured to the defect. In the second stage, the flap was divided and the frontalis muscle flap was sutured to the medial palpebral ligament. Electromyography at 1 year postoperatively confirmed neurotization of the transferred muscle, and at 6 months, voluntary contraction of the transferred muscle was observed during eyelid closure. These results suggest that a paramedian flap combined with the frontalis muscle and periosteum is a useful option for reconstructing horizontal skin defects involving the orbicularis oculi muscle.